Update of Maternal Health in Primary Care: Initial Management of Pre-Eclampsia in Primary Health Care - dr. Supriyatiningsih, M.Kes., SpOg (2016)
Membahas tentang Hipertensi Kronis, perawatan dan pengobatannya.